1988
DOI: 10.1148/radiology.169.1.3420283
|View full text |Cite
|
Sign up to set email alerts
|

Human heart: tagging with MR imaging--a method for noninvasive assessment of myocardial motion.

Abstract: Specified regions of the myocardium can be labeled in magnetic resonance (MR) imaging to serve as markers during contraction. The technique is based on locally perturbing the magnetization of the myocardium with selective radio-frequency (RF) saturation of multiple, thin tag planes during diastole followed by conventional, orthogonal-plane imaging during systole. The technique was implemented on a 0.38-T imager and tested on phantoms and volunteers. In humans, tags could be seen 60-450 msec after RF saturation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
731
0
9

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,338 publications
(740 citation statements)
references
References 0 publications
0
731
0
9
Order By: Relevance
“…On the other hand, other authors, including Augustine et al,18 using feature‐tracking, Neizel et al19 using SENC, and Kuznetsova et al20 using echocardiography found that women had similar circumferential and longitudinal strain to men. DENSE,1 tagging,8 phase contrast MR,10 and feature tracking21 use different techniques to analyze strain, which could account for some of the differences in strain values observed using these different methods 22…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, other authors, including Augustine et al,18 using feature‐tracking, Neizel et al19 using SENC, and Kuznetsova et al20 using echocardiography found that women had similar circumferential and longitudinal strain to men. DENSE,1 tagging,8 phase contrast MR,10 and feature tracking21 use different techniques to analyze strain, which could account for some of the differences in strain values observed using these different methods 22…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of ways of assessing myocardial strain with MR, including myocardial tagging,8 strain‐encoding imaging (SENC),9 phase contrast (PC) imaging,10 and DENSE 1. As a relatively new MR technique in this family, cine DENSE is capable of revealing pixel‐by‐pixel displacement and subsequently strain information of myocardial tissue from the phase data at each cardiac phase 1, 11, 12, 13.…”
mentioning
confidence: 99%
“…The one-dimensional constraints from all directions can be stacked to form the matrix equation (cf, ref. 9) [1] Y is a vector containing the one-dimensional displacements, E is a matrix containing the undeformed tag plane normals, U is a vector containing all of the three-dimensional displacement vectors to be estimated in a given time frame, and W is a zero mean noise vector with covariance matrix , which models any errors in the tag line tracking algorithm. Small values of , correspond to small errors in tag tracking.…”
Section: Spatial Coordinate Displacement Fitmentioning
confidence: 99%
“…In addition, quantifying degrees of function during stress testing or degrees of contraction asynchrony for predicting the response to cardiac resynchronization therapy can be performed (6,7). Currently, for cardiovascular magnetic resonance (CMR), MR tagging is widely used to measure myocardial strain (8,9). However, this method has some disadvantages, such as limited temporal resolution and the need for sophisticated and time-consuming methods for image processing.…”
mentioning
confidence: 99%